Diferentes usos de segundas residências: estudo de caso do loteamento Monte Aghá I em Piúma (ES) - Oliveira, Deise Thompson Lugão (2016)
The production process of coastal areas of the Northeast space Expanded South coast of Espírito Santo with the participation of second homes or vacation homes. This form of construction also nominated domicile of occasional use by IBGE (2010) is very common in the city of Piúma and stands on the national scene with one of the highest rates of households in temporary use 27.78% of total households. The neighborhood popularly known as Allotment Mont Aghá I in the municipality of Piúma developed intense urbanization from the end of the Decade of 1980, with significant participation of second homes, in the spatial organization of the neighborhood. The second homes of the place still show intense use to walk to their owners, but have, on a smaller scale, a kind of "requalification" of their duties, for different purposes, for example, fixed annual rental, borrowed or rented for work, borrowed or rented to ride and for fixed use of their owners. The results indicate that the main sources of public occupant vectors are in the States of Minas Gerais, Rio de Janeiro and the cities of the interior of the Espírito Santo. The occupant of the public allotment Mont Aghá I has different incomes, highlighting the values between 4 to 6 minimum wages for occupants to ride. Most are young between 26 to 45 years which reflects in the way that makes the use of public buildings and in the interest of this for attractions that are in addition to enjoy nature, as for example, shows, bars, restaurants, shops, and other services.